224k views
1 vote
Please explain your answer. THX!!!

Please explain your answer. THX!!!-example-1
Please explain your answer. THX!!!-example-1
Please explain your answer. THX!!!-example-2

1 Answer

3 votes

Answer:

1) cos (3x)

2)
(-(1-√(3))^(2))/(2)

Explanation:

Given expression:

cos(7x)cos(4x)+sin(7x)sin(4x)

By using the trigonometric identity

cos(a)cos(b) + sin(a)sin(b) = cos(a-b)

we have:

cos(7x)cos(4x)+sin(7x)sin(4x) = cos(7x - 4x)

= cos(3x)!

part 2:

tan (-π/12)

by using property tan(-x)= - tan(x)

=-tan(π/12)

= - tan(π/6 / 2)

Using tan(x/2) =
\sqrt{(1 - cos(x))/(1+cos(x)) }

= -
\sqrt{(1 - cos(pi/6))/(1+cos(pi/6)) }

cos π/6 =
(√(3) )/(2)

= -
\sqrt{(1-(√(3) )/(2) )/(1+(√(3) )/(2) ) }

= -
\sqrt{7-4√(3) }

= - 2+
√(3)

=
-((1-√(3)) ^(2) )/(2)

!

User Atiq Ur Rehman
by
5.2k points